Penyebaran Islam dalam Khazanah Pesantren: Analisis Kitab Ahla al-Musāmarah fī Hikāyāt al-Auliyā’ al-‘Asyrah: The Spread of Islam in Pesantren Tradition: An Analysis of the Book of Ahla al-Musāmarah fī Hikāyāt al-Auliyā' al-'Asyrah - Fuadi, Moh Ashif; Mahbub, Moh. (LP2M Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This study discusses the channel of Islamization in the traditional treasures of Pesantren, Islamic boarding schools, especially on a book by Indonesian scholar namely Kiai Abul Fadhol, Ahla al-Musāmarah fī Hikāyāt al-Auliyā' al-'Asyrah. This research uses library research by going through the book's main sources and strengthened by books, articles, and other written sources. The results of the study show that the channel of Islamization in the review of the book is through: first, the medium of marriage, like The King to a Cempan lady and marriage between members of the Walisongo family, secondly, education centered at the Pesantren Ampel Denta which produces a network of students as well as the tasawuf approach among the congregation. Furthermore, regarding the term of Wali Sepuluh (Ten Saints) stated in the title, there is no significant difference between the characters intended by the author of the book and the Walisongo figure. From the text, it can be seen that Kiai Fadhol was a prolific scholar who argued that the collapse of the Majapahit Kingdom was due to an attack from the Demak Sultanate led by Raden Patah. Finally, we can found that the character of the da'wah developed includes good wisdom and calls.